Soluble ST2 promotes oxidative stress and inflammation in cardiac fibroblasts: an in vitro and in vivo study in aortic stenosis. (17th July 2019) - Matilla, Lara; Ibarrola, Jaime; Arrieta, Vanessa; Garcia-Peña, Amaia; Martinez-Martinez, Ernesto; Sádaba, Rafael; Alvarez, Virginia; Navarro, Adela; Fernández-Celis, Amaya; Gainza, Alicia; Santamaría, Enrique; Fernández-Irigoyen, Joaquín; et al.
Abstract : Background: Soluble ST2 (interleukin 1 receptor-like 1) (sST2) is involved in inflammatory diseases and increased in heart failure (HF). We herein investigated sST2 effects on oxidative stress and inflammation in human cardiac fibroblasts and its pathological role in human aortic stenosis (AS). Methods and results: Using proteomics and immunodetection approaches, we have identified that sST2 down-regulated mitofusin-1 (MFN-1), a protein involved in mitochondrial fusion, in human cardiac fibroblasts. In parallel, sST2 increased nitrotyrosine, protein oxidation and peroxide production. Moreover, sST2 enhanced the secretion of pro-inflammatory cytokines interleukin (IL)-6, IL-1β and monocyte chemoattractant protein-1 (CCL-2). Pharmacological inhibition of transcriptional factor nuclear factor κB (NFκB) restored MFN-1 levels and improved oxidative status and inflammation in cardiac fibroblasts. Mito-Tempo, a mitochondria-specific superoxide scavenger, as well as Resveratrol, a general antioxidant, attenuated oxidative stress and inflammation induced by sST2. In myocardial biopsies from 26 AS patients, sST2 up-regulation paralleled a decrease in MFN-1. Cardiac sST2 inversely correlated with MFN-1 levels and positively associated with IL-6 and CCL-2 in myocardial biopsies from AS patients. Conclusions: sST2 affected mitochondrial fusion in human cardiac fibroblasts, increasing oxidative stress production and inflammatory markers secretion. The blockade of NFκB or mitochondrial reactive oxygen species restored MFN-1 expression, improving oxidative stress status and reducing inflammatory markers secretion. In human AS, cardiac sST2 levels associated with oxidative stress and inflammation. The present study reveals a new pathogenic pathway by which sST2 promotes oxidative stress and inflammation contributing to cardiac damage.